Corneal Epithelial Thickness Mapping in Healthy Population Corneas Using MS-39 Anterior Segment Optical Coherence Tomography - AlTurki HS; Alsubhi SS; Alhazmi A; Alhadlag A; Albalawi NS; Alzoman MA; Aljasir M; Alsubaie M; Aljindan M; Alsomali A (Clinical Ophthalmology)
Hissah Saleh AlTurki,1 Shahad Salah Alsubhi,1 Asma Alhazmi,1 Abdulrahman Alhadlag,2 Nada Saleh Albalawi,3 Musab Abdulaziz Alzoman,1 Mohammed Aljasir,1 Majed Alsubaie,1 Mohanna Aljindan,4 Abdulaziz Alsomali5 1Ophthalmology Department, Dhahran Eye Specialist Hospital, Dhahran, Saudi Arabia; 2Surgery Department, College of Medicine, Shaqra University, Riyadh, Saudi Arabia; 3Ophthalmology Department, King Salman Armed Forces Hospital, Tabuk, Saudi Arabia; 4Ophthalmology Department, College of Medicine, Imam Abdulrahman Bin Faisal University, Dammam, Saudi Arabia; 5Ophthalmology Department, College of Medicine, King Faisal University, Alahsa, Saudi ArabiaCorrespondence: Shahad Salah Alsubhi, Ophthalmology Department, Dhahran Eye Specialist Hospital, 32413, Hassan Alaslami, Ash Shati Ash Sharqi District, Dhahran, Saudi Arabia, Email Shahadsalah@hotmail.comPurpose: The corneal epithelium is the outermost layer of the cornea. It plays a vital role in both normal and pathological conditions of the eye surface and serves as a protective layer. This study aimed to evaluate corneal epithelial thickness (ET) and create a normative database of corneal ET for pediatric and adult age groups using MS-39 AS-OCT.Patients and Methods: This is a cross-sectional multi-center study conducted among the Saudi population.Results: A total of 268 eyes of 268 patients were analyzed (male 50.7% vs female 49.3%). 53.8% were pediatric age group. Higher mean values of central, paracentral, and peripheral were associated with the adult age group except for superior paracentral, temporal peripheral, and nasal peripheral. Male patients had higher mean values of central, paracentral, and peripheral in each quadrant, except for inferior peripheral. There was a significant correlation between inferior, superior, nasal, and temporal in both paracentral and peripheral. No significant correlations were observed between the spherical equivalent and epithelial thickness map.Conclusion: The study found sex differences, with females generally having lower ET values than males, and older age having higher values than children.Keywords: corneal epithelial thickness, anterior segment, optical coherence tomography, Saudi Arabia